The impact of privatisation on union membership and density: A Western Australian case study - Oliver, Bobbie (Sage Publications Ltd., 2014)
Falling membership numbers and declining union density are issues of concern for many Australian unions. Australian Bureau of Statistics figures show that between 2005 and 2008, trade union membership declined from 22.4% to 18.9% of the workforce. Studies and statistics consistently show that union membership and density are lowest in Western Australia, despite trend reversals elsewhere. Using the Western Australian branches of two 'blue-collar' unions - the Australian Rail, Tram and Bus Industry Union, Western Australian Branch and the Australian Manufacturing Workers' Union, covering a range of transport, metal working, printing and manufacturing trades - as examples, this article examines whether privatisation has contributed significantly to falling trade union density and membership in this state. These unions represented large public sector workforces. In order to test the hypothesis that privatisation has adversely affected union membership and density, the article examines three areas: changing policies in the Australian Labor Party, the breaking down of union culture and changes in trade training, and concludes that privatisation is a significant factor in the recent decline of these two unions.